Visualisasi Bunga Mawar Melalui Teknik Sulam Pita Dan Bordir Sebagai Hiasan Dinding - CINDY MEUTHIA FARIZA, Dra. Minarsih, M.Sn., Drs. Erwin A, M.Sn. (Serupa The Journal of Art Education, 2016)
Roses are also known as rose or the "queen of flowers". The roseis one of ornamental crops, which can be made into a beautifulyard. The beauty contained in the form of roses expressive andvisualize them via ribbon embroidery techniques and embroidery, will be born expressive forms show the personality style that creates the artwork. The work in the form Fine-Craft that prioritizes individual expression. Thus, the title of this thesis is "Visualization roses Through Ribbon embroidery techniques and embroidery as Wall Hanging". The creation of this work aims to visualize the beauty of roses with ribbon embroidery techniques and embroidery as wall hangings. Time in making this thesis starts from May to July 2016. The resulting work is as much as 7 work wall hangings, with the theme of roses displayed in a variety of species of roses. The title of the work produced is courage, gratitude, happiness, gratitude, joy, passion and harmony.Keywords: Roses, Ribbon Embroidery, Embroidery